Analysis Of Husband’s Support For The Application Of Pregnancy Class At Home Towards Preparation For Delivery Of Pregnant Women In The Trimester III In The Work Area Of Kandangan Public Health Center, Kediri Regency - Wahyuni, Candra; Wiji Andayani (Journal of Global Research in Public Health, 2017)
Low maternal knowledge about the benefits of prenatal exercise so that pregnant women do not take prenatal classes. Many pregnant women do not take prenatal classes because no one accompanies them because other family members, especially their husbands, are at work. Husbands have a significant role in the compliance of pregnant women in taking prenatal classes. To improve the implementation of prenatal classes, it can be done by increasing several factors that can influence the implementation of prenatal classes in Trimester III, including increasing the role of the family, especially husband's support. The purpose of this study was to analyze the relationship between husband's support for the application of prenatal classes at home and preparation for childbirth for pregnant women in Trimester III. This study uses a quantitative research method using a cross-sectional approach. The population studied were pregnant women in the third trimester in March in the Kandangan Health Center Work Area, Kediri Regency, totaling 35 people, using the total sampling technique. With the independent variable being husband's support for the application of prenatal classes at home, and the dependent variable being preparation for childbirth for pregnant women in the third trimester. The research results were analyzed using the Mann-Whitney test statistically, it was found that the Exact Sig.(2-tailed) p value obtained a result of 0.41, which means that the Exact Sig.(2-tailed) p value < 0.05, soaccepted means there is a relationshipH_1Husband's support for the application of home pregnancy classes for preparing pregnant women for childbirth in the third trimesterin the working area of the Kandangan Health Center, Kediri Regency.Husband's support is the most dominant factor influencing the participation of pregnant women in pregnancy classes. Motivation and support from the husband are things that influence the preparation of childbirth for pregnant women in the third trimester in applying pregnancy classes at home. When the husband supports and is involved in implementing pregnancy exercises at home, it can make pregnant women in the third trimester more prepared to face childbirth.